Psychometric properties of the olson and barnes quality of life scale in lima students - Grimaldo, Mirian Pilar (2020)
Quality of life refers to the way in which the person perceives their daily experience, considering in this process the social and cultural component. This implies that to know the perception of the quality of life it is necessary to consider in its measurement the scope of physical, psychological, social, environmental and personal health. Along these lines, one of the instruments that is limited to this approach is the Barnes and Olson Quality of Life Scale (ECVOB). Objective. The purpose of the study was to determine the validity based on the internal structure and reliability of the ECVOB in schoolchildren and university students in Lima. Method. The study design is instrumental. The Spanish version of the ECVOB was used on a sample of 1239 students from Lima between males (57%) and females (43%) aged between 14 and 26 years (M age = 22.45; SD age = 3.75). The evidence of validity of the internal structure was evaluated through a confirmatory factor analysis. Results. The findings suggest a partial restructuring of the original seven-factor model proposed by Olson and Barnes. Conclusion. The new structure of the ECVOB is a valid and reliable measure in schoolchildren and university students in Lima.